Dental Implant Macrogeometry and Biomaterials - Calvo Guirado, José Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Dental implant treatments are widely used and can be an option for lost teeth. Most treatment alternatives are limited due to bone structure, bone density, and patient's health condition. This book is focused on simple and complicated clinical cases, different types and designs of implants, and also the way to obtain bone-to-implant contact. We have also sought to assess different biomaterials, bone stimulators, and types of dental implants that can reduce the gap, protect the peri-implant bone, and increase the aesthetics. The relationship of bone formation and biomaterials with dental implants is the key factor in bringing back the full reconstruction of soft and hard tissues. Additionally, the type of materials used for implant development are extremely important, especially in relation to strength and bending forces. The contact and protection of bundle bone with both biomaterials and implants will provide highly predictable success in aesthetics and function.